Bio-based phenols and fuel production from catalytic microwave pyrolysis of lignin by activated carbons - Bu, Quan; Lei, Hanwu; Wang, Lu; Wei, Yi; Zhu, Lei; Zhang, Xuesong; Liu, Yupeng; Yadavalli, Gayatri; Tang, Juming (Bioresource technology, 2014)
•Catalytic microwave pyrolysis of lignin from activated carbon was investigated.•45% of phenol, 78% of total phenolics, and 15.3% of hydrocarbons were achieved.•The heating value of lignin-derived biochars was significantly higher than lignin.•The thermal degradation and reaction mechanism were analyzed. The aim of this study is to explore catalytic microwave pyrolysis of lignin for renewable phenols and fuels using activated carbon (AC) as a catalyst. A central composite experimental design (CCD) was used to optimize the reaction condition. The effects of reaction temperature and weight hourly space velocity (WHSV, h−1) on product yields were investigated. GC/MS analysis showed that the main chemical compounds of bio-oils were phenols, guaiacols, hydrocarbons and esters, most of which were ranged from 71% to 87% of the bio-oils depending on different reaction conditions. Bio-oils with high concentrations of phenol (45% in the bio-oil) were obtained. The calorific value analysis revealed that the high heating values (HHV) of the lignin-derived biochars were from 20.4 to 24.5MJ/kg in comparison with raw lignin (19MJ/kg). The reaction mechanism of this process was analyzed.